Microfiber Sagnac Interferometer for sensing applications - Kuczkowski, Michal; Ying, Cui; Quyen Dinh, Xuan; Shum, Perry Ping; Rutkowska, Katarzyna A.; Woliński, Tomasz R. (Photonics Letters of Poland, 2012)
In this paper we propose an optical fiber-based refractive index and temperature sensor using an MNF (micro/nano fiber) inserted in a Sagnac loop interferometer [1]. A portion of the PMF is tapered into a micro/nano dimension to increase the interactions between a guided signal and the surrounding environment. Experimental tests have demonstrated low response to temperature and high sensitivity to refractive index change of a liquid surrounding the MNF. It has been shown that the sensitivity of the setup under test to temperature decreases when a longer MNF is used. The maximum sensitivity for a refractive index achieved equals to 1068nm/RIU, which was obtained by a 4.7-mm long MNF with a diameter of 30um. Full Text: PDF References G. Wang, P.P. Shum, L. Tong, C.M. Li; C. Lin, "Polarization Effects in Microfiber Loop and Knot Resonators", IEEE Phot. Tech. Lett. 22, 586 (2010). CrossRef L. M. Tong, M. Sumetsky, Subwavelength and Nanometer Diameter Optical Fibers (Zhejiang University Press, Springer 2009). H. Gong, C.C. Chan, L. Chen, X. Dong, "Strain Sensor Realized by Using Low-Birefringence Photonic-Crystal-Fiber-Based Sagnac Loop" IEEE Phot. Tech. Lett. 22(16), 1238 (2010). CrossRef X. Dong, H. Tam, P. Shum, "Temperature-insensitive strain sensor with polarization-maintaining photonic crystal fiber based Sagnac interferometer", Appl. Phys. Lett. 90, 151113 (2007). CrossRef C. E. Chryssou, "Theoretical analysis of tapering fused silica optical fibers using a carbon dioxide laser", Opt. Eng. 38(10), 1645 (1999). CrossRef K. Milenko et al., "Photonic crystal fiber tip interferometer for refractive index sensing", Opt. Lett. 37(8), 1373 (2012). CrossRef Y. Zong et al., "Refractive index sensing based on higher-order mode reflection of a microfiber Bragg grating", Opt. Exp. 18(25), 26345 (2010). CrossRef D. Wu et al., "Refractive index sensing based on Mach?Zehnder interferometer formed by three cascaded single-mode fiber tapers", Appl. Opt. 50(11), 1548 (2011). CrossRef X. Guo, L. Tong, "Supported microfiber loops for optical sensing", Opt. Exp. 16(19), 14429 (2008). CrossRef J. Zhan et al., "Highly Sensitive Temperature Sensor Using PANDA Fiber Sagnac Interferometer", J. Lightwave Technol. 29(24), 3640 (2011). CrossRef O. Fraz?o, J.M.T. Baptista, J.L. Santos, "Recent Advances in High-Birefringence Fiber Loop Mirror Sensors", Sensors 7, 2970 (2007). CrossRef